Synthesis and characterization of γ-Fe2O3 NPs on silicon substrate for power device application - Abu Hussein, Nurul Athirah (IOP Publishing, 2018)
Maghemite nanoparticles (γ-Fe 2 O 3 NPs) were synthesized using Massart procedure. The formation reaction were optimized by varying the concentration of ferric nitrate solution (Fe(NO 3 ) 3 ) (0.1, 0.3, 0.5, 0.7 and 1.0 M). All samples were characterized by means of x-ray Diffractometer (XRD), Raman Spectroscopy, Transmission Electron Microscope (TEM) and Alternating Gradient Magnetometer (AGM). The smallest size of the NPs were chosen to be deposited on Silicon (100) substrate by spin coating technique. Annealing process of the samples were performed in Argon ambient at different temperatures (600, 700, 800 and 900°) for 20 min. Metal-oxide-semiconductor capacitors were then fabricated by depositing Aluminium as the gate electrode. The effect of the annealing process on the structural and electrical properties of γ-Fe 2 O 3 NPs thin film were investigated. The structural properties of the deposited thin film were evaluated by XRD analysis, Atomic Force Microscopy (AFM) and Raman Analysis. On the other hand, the electrical properties was conducted by current-voltage analysis. It was revealed that the difference in the annealing temperature affect the grain size, surface roughness, distribution of the nanoparticles as well as the electrical performance of the samples where low annealing temperature (600 °C) gives low leakage current while high annealing temperature (900 °C) gives high electrical breakdown.